Studies on the Influence of Pseudomonas fluorescens and Chemicals on the Biocontrol Sheath Blight Incidence in Rice - Sivakamasundari, R (International Journal of Pharmaceutical & Biological Archive, 2012)
Studies on the Influence of Pseudomonas fluorescens and Chemicals on the Biocontrol Sheath Blight Incidence in Rice